2006
DOI: 10.1007/s10661-006-5030-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of New Vehicles Emissions Certification Standards in the Metropolitan Area of Mexico City

Abstract: Light duty gasoline vehicles account for most of CO hydrocarbons and NOx emissions at the Metropolitan Area of Mexico City (MAMC). In order to ameliorate air pollution from the beginning of 2001, Tier 1 emission standards became mandatory for all new model year sold in the country. Car manufacturers in Mexico do not guarantee the performance of their exhaust emissions systems for a given mileage. The purpose of this study was to assess whether the Tier 1 vehicles will stand the certification values for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In 1997, discussions between INE and Mexican Vehicle Manufacturers Association (Asociacion de la Industria Automotriz (AMIA) began to develop further emissions standards closer to those in the USA for introduction in 1999 (Fernandez-Bremauntz, 2008). AMIA disagreed with the new standards, contending that the cost of satisfying them would be excessive and that they would require until at least 2001 or longer to develop air pollution management capacities (Schifter et al, 2006). It suggested that, for a number of reasons, including Mexico City's valley location and altitude, the fuel parameters and the excessive cost of updating air pollution management technologies, it would be challenging at best, and more likely unfeasible at worst, to be able to adhere to the standards by the proposed date of introduction (Schifter et al, 2006).…”
Section: Transportation Air Pollution Management Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1997, discussions between INE and Mexican Vehicle Manufacturers Association (Asociacion de la Industria Automotriz (AMIA) began to develop further emissions standards closer to those in the USA for introduction in 1999 (Fernandez-Bremauntz, 2008). AMIA disagreed with the new standards, contending that the cost of satisfying them would be excessive and that they would require until at least 2001 or longer to develop air pollution management capacities (Schifter et al, 2006). It suggested that, for a number of reasons, including Mexico City's valley location and altitude, the fuel parameters and the excessive cost of updating air pollution management technologies, it would be challenging at best, and more likely unfeasible at worst, to be able to adhere to the standards by the proposed date of introduction (Schifter et al, 2006).…”
Section: Transportation Air Pollution Management Strategiesmentioning
confidence: 99%
“…AMIA disagreed with the new standards, contending that the cost of satisfying them would be excessive and that they would require until at least 2001 or longer to develop air pollution management capacities (Schifter et al, 2006). It suggested that, for a number of reasons, including Mexico City's valley location and altitude, the fuel parameters and the excessive cost of updating air pollution management technologies, it would be challenging at best, and more likely unfeasible at worst, to be able to adhere to the standards by the proposed date of introduction (Schifter et al, 2006). Further to this, vehicle manufacturers emphasised that Mexico's environmental officials should be more concerned with actions designed to phaseout the use of carburettors in older, less efficient cars, which are responsible for a much higher proportion of air pollution than newer, more modern cars fitted with catalytic converters (Fernandez-Bremauntz, 2008).…”
Section: Transportation Air Pollution Management Strategiesmentioning
confidence: 99%
See 2 more Smart Citations